Thermophysical properties of sustainable cement mortar containing oil palm boiler clinker (OPBC) as a fine aggregate. (25th January 2021) - Asadi, Iman; Shafigh, Payam; Hashemi, Mohammad; Akhiani, Amir Reza; Maghfouri, Mehdi; Sajadi, Behrang; Mahyuddin, Norhayati; Esfandiari, Masoud; Rezaei Talebi, Hamed; Metselaar, Hendrik Simon Cornelis
Graphical abstract: Highlights: The normal sand was replaced by Oil Palm Boiler Clinker (OPBC) as a by-product fine aggregate. Thermal conductivity of OPBC mortar decreased by 72%. Specific heat capacity of OPBC mortar increased by 41%. Thermal diffusivity of OPBC mortar decreased 76%. Abstract: This study investigated the thermophysical properties in terms of thermal conductivity, heat capacity, thermal diffusivity, density, compressive strength, water absorption, and sorptivity of cement mortars containing different percentages of oil palm boiler clinker (OPBC). The normal sand was replaced by 25%, 50%, 75%, and 100% of OPBC. Furthermore, the relation between the thermal properties of mortar containing various amounts of OPBC with its physical properties has been discussed. The results indicated that 100% replacement of sand by OPBC decreases the density, thermal conductivity, and thermal diffusivity of cement mortar around 16%, 72%, and 76%, respectively. Moreover, the findings revealed that the specific heat capacity of the mortar increases by around 41%, while the sand is replaced by OPBC in 100%. Based on the findings, the usage of OPBC as fine aggregate affects the thermophysical properties of cement mortar due to the higher porosity of OPBC in comparison with normal sand. Therefore, it can be concluded that OPBC mortar can be used as a sustainable and energy-efficient building material due to its decent thermal properties.